2005
DOI: 10.18388/abp.2005_3452
|View full text |Cite
|
Sign up to set email alerts
|

Store-operated calcium entry in physiology and pathology of mammalian cells.

Abstract: One of the numerous calcium-involving processes in mammalian cells is store-operated calcium entry (SOCE) -- the process in which depletion of calcium stores in the endoplasmic reticulum (ER) induces calcium influx from the extracellular space. Previously supposed to function only in non-excitable cells, SOCE is now known to play a role also in such excitable cells as neurons, muscles and neuroendocrine cells and is found in many different cell types. SOCE participates not only in processes dependent on ER cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 102 publications
1
20
0
Order By: Relevance
“…It has been reported that STIM1 and Orai1 are the key components responsible for SOCE in many non-excitable cell types ( Targos et al, 2005 ; McCarl et al, 2010 ; Putney et al, 2017 ); STIM1, STIM2, and Orai1 are the main subunits of SOCs mediating SOCE in CNS neurons ( Berna-Erro et al, 2009 ; Klejman et al, 2009 ; Xia et al, 2014 ). Our RT-qPCR and Western blot results have demonstrated that the SOC family members are differentially expressed in DRGs from adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that STIM1 and Orai1 are the key components responsible for SOCE in many non-excitable cell types ( Targos et al, 2005 ; McCarl et al, 2010 ; Putney et al, 2017 ); STIM1, STIM2, and Orai1 are the main subunits of SOCs mediating SOCE in CNS neurons ( Berna-Erro et al, 2009 ; Klejman et al, 2009 ; Xia et al, 2014 ). Our RT-qPCR and Western blot results have demonstrated that the SOC family members are differentially expressed in DRGs from adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Foremost, TRPC1 channels in combination with ORAI1 have been implicated in CICR. [22,[34][35][36][37][38][39] TRPA1 has also been described to contribute to CICR. [40] In order to ascertain TRP channel expression in CDVs, parallel reaction monitoring (PRM) was used to specifically detect proteotypic peptides mapping to TRPC1, ORAI, TRPA1, TRPV1 or TRPV2.…”
Section: Proteome Analysismentioning
confidence: 99%
“…) and has been shown to be involved in conditions such as neuropathic pain, ischaemic stroke, Parkinson's disease and Alzheimer's disease (Targos et al . ; Berna‐Erro et al . ; Selvaraj et al .…”
Section: Introductionmentioning
confidence: 99%